Tolerância à salinidade e capacidade de absorção de potássio de genótipos de arroz irrigado. - Sanes, Fernanda San Martins (2009)
The rice is the cultivated and consumed cereals more in Brazil. In the coastal region, the adverse effect of salinity can cause decrease in plant growth and nutrients uptake, being that the absorption capacity, mainly of K, that is one of the main nutrients for the culture of the rice irrigated, is the result of the tax of absorption for unit of length of roots, as well as its morphology. With the objective of this study was to evaluate rice genotypes with respect to salts tolerance in irrigation water and with different K uptake, two studies, being one experiment was developed in an experimental area of Embrapa Clima Temperado, Capão do Leão, RS, in tanks of masonry, where a surface layer of an Albaqualf soil was deposited. The treatments applied from the time of differentiation panicle to physiological maturity: plant irrigation with drinking water, water with 0.25% NaCl and water with 0.5% NaCl, arranged in a completely randomized design, with three replications. There were evaluated twelve rice genotypes: BRS Querência, BRS Atalanta, BRS Bojuru, BRS Fronteira, CNA 10754, CNA 10756, CNA 10757, BRA 1455, BRA 1024, BRA 1073, Avaxi. The Inov hybrid was only evaluated in the salinity experiment. In the first study. To the ending of the cycle of each genotype, the degree tolerance to the salinity the irrigation water was evaluated, for diagnose visual, evaluation of the productivity and text nutrients of each to cultivate. On the basis visual evaluation intensity of symptoms of damages for excess salt applied in the water irrigation in the period of differentiation panicle physiological maturity, all the genotypes are tolerant to the average level of salinity (0.25% of NaCl). In the high level (0.50% of NaCl), the genotypes `Avaxi', BRA 1024, `BRS Atalanta', `BRS Bojuru', `BRS Fronteira', CNA 10756 and `Inov' moderately classify as tolerant and BRA 1073 BRA 1455, `BRS Querência', CNA 10754 and moderately susceptible CNA 10757 as. The sterility of spikelet varies with the rice genotype, being distinguished to cultivate it BRS Bojuru, as only with inferior index 50%. Under the level highest salt in the irrigation water, the dry mass of the rice plants is reduced, having variations, still, between the genotypes. The text of sodium in the stalk and leves and the grains of rice increases with the concentration of salt in the irrigation water, the opposite occurring for the magnesium concentration. The increase of the salinity in the irrigation water increases texts of in the exchangeable one, the percentage of saturation for sodium and the electrical conductivity of the extract of saturation of the ground, not influencing the exchangeable concentration of excessively cations. In the study of the difference of capacity of absorption of K, The experiment was set up in an entirely randomized experimental design, with three repetitions. The amount of potassium absorbed for the genotypes of irrigated rice directly is related with area and the root length and development of the aerial part. The kinetic parameters of potassium absorption, Imax, km and Cmin, had varied between the genotypes resulting in three distinct groups how much to the tax of potassium accumulated. The group of bigger capacity of potassium uptake is formed by genotypes BRS Atalanta, BRS Querência, Avaxi, BRA 1073 and BRA 1455. The main responsible kinetic parameter for the biggest capacity of potassium uptake for cultivating BRS Atalanta is the Imax. The growth root, of genotypes Avaxi , BRS Querência , BRA 1073 and BRA 1455, compensated the lesser tax of absorption.